Development of an environmental quality index using satellite technology for sugarcane areas: the case of San Luis Potosí, México - Pérez Medina, Pedro; Quiroz Gaspar, Ángel de Jesús; Galindo Mendoza, María Guadalupe (Acta Universitaria, 2023)
Satellite monitoring to generate environmental quality indices is an affordable and relevant technique to understand the impact of anthropogenic activities on the environment. Recently, its usefulness has been increased by the development of tools such as Google Earth Engine. The objective of this study is to propose an environmental quality index in areas where ecosystem services are affected by sugarcane production. Four variables were included in the design: black carbon, normalized burned area index, improved vegetation index, and soil temperature. The proposal resulted in an ordinal scale of five levels of environmental quality ranging from “very poor quality” to “very good quality”. The sugarcane area of San Luis Potosí was used as a case study for the 2021-2022 harvest. The analysis showed that air quality generally improves to “good” during the non-harvest months. It is recommended to continue experimenting with more variables and to extend the analysis period to consolidate the results.